LITERATURE STUDY OF ANTIBACTERIAL ASSAY OF AVERRHOA BILIMBI L. AGAINST GRAM POSITIVE BACTERIA - Sari, Erwika Dwika; Kosman, Rachmat; Herwin, Herwin (Journal Microbiology Science, 2022)
Averrhoa bilimbi L. is one of the traditional medicines that people empirically use as medicine to treat various diseases such as cough, diabetes, rheumatism, mumps, canker sores, toothache, bleeding gums, acne, diarrhea to high blood pressure. The research aimed to determine the antibacterial activity of Averrhoa bilimbi L. against gram-positive bacteria. This research applied a literature study method in which the references were obtained from 3 data bases, namely google scholar, pubmed and mdpi, then selected journals that metthe criteria in the literature study.  From the journal exploration, 7 journals were obtained. Then the antibacterial activity of Averrhoa bilimbi L. against gram-positive bacteria was observed. The results confirmed that the fruit and leaves of Averrhoa bilimbi L. had an antibacterial activity against Staphylococcus aureus, Streptococcus mutans, Staphylococcus epidermidis, and Propionibacterium acnes due to the presence of secondary metabolites, namely saponins, tannins, alkaloids and flavonoid.